Elective Induction of Labor and Postpartum Hemorrhage in Females Presenting for Normal Vaginal Delivery at Term - Shabana Bano Soomro, Fahmida Mahar, Tanweer Akhtar, Sania, Fozia Unar, Fouzia Begum, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Labor induction is the process or treatment that stimulates childbirth and delivery. Induction of labor without a medical indication is termed elective induction of labor and appears to be increasing even more rapidly than induction of labor as a whole. Postpartum hemorrhage (PPH) leads to prominent causes of maternal death. Uterine massage is a simple first line treatment as it helps the uterus to contract to reduce bleeding. Objectives: To determine the frequency of elective induction of labor in females undergoing normal vaginal delivery at term and to compare the frequency of postpartum hemorrhage with spontaneous versus elective induced labor in females presenting for normal vaginal delivery at term. Study Design: Descriptive case series study Place and Duration of Study: Department of Obstetrics & Gynecology, Shaikh Zayed Women Hospital, Larkana from 1st October 2021 to 31st March 2022. Methodology: Two hundred females were enrolled. They were divided in two groups; elective induction or spontaneous delivery. Females who had active labour without oxytocin with no membrane rupture before labour, labeled as having spontaneous labour otherwise. Results: The induced delivery was noted in 35(17.50%) females and spontaneous type of delivery was noted in 165(82.50%) females, the postpartum hemorrhage was noted among 23(11.50%) females. The postpartum hemorrhage is not associated with type of delivery (p=0.249). Conclusion: The elective induction of labor in females undergoing normal vaginal delivery at term was 17.50% patients and postpartum hemorrhage was 11.50% patients. Keywords: Postpartum hemorrhage, Postpartum hemorrhage (PPH), Spontaneous, Induced, Labour, Delivery